2018
DOI: 10.1158/0008-5472.can-17-2001
|View full text |Cite
|
Sign up to set email alerts
|

Restraining Network Response to Targeted Cancer Therapies Improves Efficacy and Reduces Cellular Resistance

Abstract: A key tool of cancer therapy has been targeted inhibition of oncogene-addicted pathways. However, efficacy has been limited by progressive emergence of resistance as transformed cells adapt. Here, we use to dissect response to targeted therapies. Treatment with a range of kinase inhibitors led to hyperactivation of overall cellular networks, resulting in emergent resistance and expression of stem cell markers, including Sox2. Genetic and drug screens revealed that inhibitors of histone deacetylases, proteasome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…To overcome the drug resistance and serious side effects of chemotherapy, a combined treatment approach holds promise for achieving a synergistic anticancer benefit . Das et al …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome the drug resistance and serious side effects of chemotherapy, a combined treatment approach holds promise for achieving a synergistic anticancer benefit . Das et al …”
Section: Discussionmentioning
confidence: 99%
“…To overcome the drug resistance and serious side effects of chemotherapy, a combined treatment approach holds promise for achieving a synergistic anticancer benefit. 26 Das et al 27 showed pairing targeted therapeutics with subtherapeutic doses of broad acting "network brake" drugs extended therapeutic utility while reducing whole body toxicity. Since its first discovery, CY has been used as an anticancer drug for more than 40 years in clinical practice, and remains to be a main chemotherapy drug for multiple cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic approach to addressing therapy‐induced resistance, Das et al used the above‐described Drosophila RET‐driven tumor model wherein expression of a cancer‐relevant mutant form of Drosophila Ret, dRet MEN2B , in larval epithelial tissues resulted in partial lethality between embryo and pupa stages (Das, Esernio, & Cagan, ). Here, the authors used the Drosophila RET model to ask what OTHER signaling pathways become activated/repressed in response to treatment with a known/approved drug.…”
Section: Why Flies?mentioning
confidence: 99%
“…Further, the effect of modulating network components in the normal cells of the larvae can be tested using Drosophila genetics, thus identifying common and unique cellular responses that could explain toxicity and resistance. Once a functionally relevant network has been identified, the authors used known inhibitors to retrain the network to non‐drug levels, so‐called “network breaks,” with the goal of reducing toxicity or resistance (Das et al, ). For example, sorafenib, a poly‐kinase inhibitor approved for the treatment of kidney, liver and thyroid cancers, activated a network that consisted of Erk, Src, and Akt among others.…”
Section: Why Flies?mentioning
confidence: 99%
“…Finally, Bangi [12] reviews how Drosophila can be utilised to functionally analyse the vast amount of human cancer Omics data that is currently being generated, in order to validate key genes/pathways that contribute to cancer, to build new models to interrogate cancer mechanisms, and to screen for novel cancer therapeutics. Drosophila has already proven its worth in identifying novel drugs that target particular types of human cancers, such as multiple endocrine neoplasia type 2 (MEN2), colorectal and non-small cell lung cancers [36][37][38][39][40][41][42], and undoubtably, the development of more sophisticated Drosophila models that incorporate additional genetic lesions will enable better modelling of human cancers and new anti-cancer drug discovery.…”
mentioning
confidence: 99%